Pengaruh Kinerja Keuangan terhadap Nilai Perusahaan di Perusahaan Industri Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia - Lybryanta, Ocktav Andrian; Toha, Akhmad; Sisbintari, Ika (e-Sospol, 2015)
Abstract This research was aimed to determine the effect of financial performance on company's value and the effect of dividend policy in the relationship of financial performance on the company's value. This research was hypothesis testing-based research. The data used in this research were secondary data. In managing and analyzing data were used descriptive statistics and multiple linear regression analysis. The results of the processed and analyzed data can be used as an answer framework for the determined hypotheses. Data analysis techniques used to solve problems in this research were descriptive statistics, classical assumption test, multiple linear regression analysis, Moderated Regression Analysis (MRA), and hypothesis test that consisted of t-test and F-test. These analyses were used to identify and obtain a description of the effect of financial performance on company's value with the dividend policy as a moderating variable. The research results explained that partially and simultaneously financial performance was able to significantly affect the company’s value, that partially dividend policy was not able to moderate the effect of financial performance on the company's value, and that simultaneously dividend policy was able to significantly moderate the effect of financial performance on the company’s value.